Hypothyroidism and dysfunction of peripheral nervous system (Journal of Dhaka National Medical College & Hospital, 2016)
Current research indicates peripheral nerve dysfunction is a well-documented feature of clinical hypothyroidism. In hypothyroid patients, median motor and sensory nerves are commonly affected. Sensorimotor nerve conduction impairment occurs in hypothyroidism and the degree of impairment might be related to the degree of thyroid deficiency. It is suggested that neuropathy is not an uncommon manifestation in the newly diagnosed hypothyroidismJ. Dhaka National Med. Coll. Hos. 2016; 22 (01): 53-55